Advanced Mueller matrix ellipsometry: Instrumentation and emerging applications - Chen, XiuGuo; Gu, HongGang; Liu, JiaMin; Chen, Chao; Liu, ShiYuan (Science China. Technological sciences, 2022)
Mueller matrix ellipsometry (MME) provides the 4×4 Mueller matrix of a sample under test, which determines how the state of polarization is changed as light interacts with the sample. Due to the redundant information contained in the Mueller matrix, MME has gained more and more extensive applications in the characterization of surfaces, interfaces, thin films, and nanostructures. In addition, the instrumentation of MME has also achieved great developments since its advent in the 1970s. In this paper, we will first review the basic principle as well as the common system layouts of MME for the full Mueller matrix measurement. Then, the basic procedure of ellipsometry data analysis is reviewed. After that, some new developments in MME in our lab for different applications are introduced, including the broadband MME, the high-resolution imaging MME, and the high-speed MME. Some emerging applications of the developed MMEs are also presented. Conclusions and perspectives of the advanced ellipsometry are finally drawn and discussed.